A Study of the production system of Licton Industrial Corporaton - Ben, Rolly D. (College of Engineering, 2002)
Licton Industrial Corporation (LIC) started in 1978 with 2 blown-film extrusion machines and one product, "sando" plastic bags. Now it has 40 extrusion machines, 12 injection molding machines, a printing facility, and the only CO-EXTRUSION machine in the Philippines. It serves clients such as SM Supermalls, Mercury Drug, Gaisano, and the Philippine Dairy Products Corporation (PDPC).This project concentrates on the Production and Operations Management issues of the Injection Molding Business. The Injection Molding Business (IMB) is a semi-independent, detached facility of LIC that produces the canisters and lids used by the PDPC for its Star Margarine line. Canisters and lids of three colors (yellow, orange and green) and of three sizes (100-gram, 250-gram, 1-kilogram) are processed 24 hours daily. Because the IMB has only one client, it gives emphasis to low-cost operations, on-time delivery, and consistent product quality. By documentation and problem analysis, three problems are verified for existence in the system: 1. High monthly aggregate inventory value, estimated at an average of P2.4 million, 2. Excessive (and unbalanced) machine utilization leading to monthly overtime costs of P20,000, 3. Stock-outs of packing materials, increasing risks of pilferage, damage, and inability of the company to deliver on time. Three P/OM issues are found (by streamline diagnosis) to be major causes: 1. Absence of internal forecasting, 2. Absence of aggregate planning, 3. Absence of an inventory system. In response to the system problems detected, a target approach was developed with a corresponding detailed algorithm called a block plan. the block plan starts off by finding a sound forecasting technique that substantially reacts to abrupt demand shifts without causing system nervousness. Next, the optimal assignment of products to machines was found using the Operations Research Model, the Assignment Method. With an optimal assignment on hand, the theoretical number of workers was calculated. The evaluation of workforce management strategies followed, with the eventual conclusion that keeping the workforce number constant (at predetermined requirements) reduces costs. As part of this phase, the effectiveness of generating a Master Production Schedule (MPS) was exemplified. The development of the block plan had been molded around the alternative of having an MRP environment in the IMB. AN MRP targets the third problem of stock-outs and is the sole alternative that the team could produce so that goal congruence is achieved for the entire company. The block plan resulted to: 1. A 20% reduction in monthly aggregate inventory value (with more to be expected with the subsequent evaluation of the MRP), 2. A 100% reduction in overtimes 3. A dramatic reduction in machine utilization rates from a frequent 100% to 70% 4. The realization that the system has capacity in excess. LIC is currently laying the foundation for IMB's expansion. As more products and clients are accommodated, the value of the block plan increases. Production and operations planning does not make the system impervious to unpredictable changes; what it does is to make the system prepared for these abrupt changes so that minimal damage is caused.